Percobaan Sintesis 4-(4-Metoksibenzilidena) 2-metiloksazol-5-on dari Asetilglisin dan 4-Metoksibenzaldehid - Arrahman, Arif; Hayun, Hayun; Yanuar, Arry (UI Scholars Hub, 2011)
Compound 4-(4-methoxybenzylidene)-2-methyloxazole-5-one was one of oxazolone moety derivative. Oxazolones had several different pharmacological activity depend on substituent which was bonded to oxazolone ring. Oxazolones was an important precursor for synthesizing several compounds which had pharmacological activity. For that reason, experiment to synthesize 4-(4-methoxybenzylidene)-2-methyloxazole-5-one from acetyl- glicine and 4-methoxybenzaldehyde as an oxazolone derivative become necessary. Com- pound 4-(4-methoxybenzylidene)-2-methyloxazole-5-one was synthesized over two step of reaction. First step was reacted glycine with acetic anhydride in acidic environment yielded acetylglycine. Second step was reacted acetylglycine with 4-methoxybenzaldehyde yielded 4-(4-methoxybenzylidene)-2-methyloxazole-5-one. The product, which was collected in every step, was purified by washing and recrystalization then the purification to be tested by examining melting range and thin layer chromatography. The compound was eluci- dated by using infrared spectrophotometry and 1H-NMR spectrophotometry. Synthesis of 4-(4-methoxybenzylidene)-2-methyloxazole-5-one yielded rendement over 0,54%. The interpretation of infrared spectrum indicated that the compound which synthesized was different from the former compound but the interpretation of 1H-NMR spectrum indicated that the compound could not be ascertained as 4-(4-methoxybenzylidene)-2-methyloxa- zole-5-one because of there were impurities.